Scope of Development of Vaccine against Antibiotic Resistant Klebsiella pneumoniae: Current Perspective - Chowdhury, Md Zaforullah (Bangladesh Journal of Medical Microbiology, 2023)
Abstract Not Available Bangladesh Journal of Medical Microbiology, January 2023;17(1):1-2